Influence of innate sludge factors and ambient environmental parameters in biosolids storage on indicator bacteria survival: A review - Fane, Sarah Elizabeth; Vale, Peter C. J.; Bajón Fernández, Yadira; Cartmell, Elise; Harris, Jim A.; Tyrrel, Sean (Springer, 2019)
The potential health risks associated with sludge cake application to agricultural land are managed by controlling the levels of Escherichia coli (E. coli) bacteria which indicate the risk of pathogen transfer. Analyses undertaken following post-digestion sludge dewatering have shown unpredictable levels of E. coli increase in stored sludge cake. Presently there is limited understanding on environmental parameters controlling the indicator bacteria density in storage and the contributory effects dewatering may have. This review aims to establish the state of current knowledge on innate and environmental factors influencing E. coli dynamics and survival in biosolids. A key factor identified is the effect of mechanical dewatering processes, which transform the sludge matrix environmental conditions through the increased availability of growth factors (e.g. nutrient and oxygen). Examples of storage practices from the agricultural and food industries are also discussed as successful methods to inhibit bacterial growth and survival, which could be extrapolated to the biosolids sector to regulate E. coli concentrations.
Keywords: Biosolids; Sludge treatment; Modified atmosphere; Nutrient availability; Storage; Temperature